O Bóson de Higgs no contexto do modelo 331 supersimétrico reduzido - Ferreira Júnior, José Geilson (2016)
In this work we built a supersymmetric version of the recently proposed reduced minimal 3-3-1 model using the superfield formalism. We study the mass spectrum of all particles emphasizing on the mass spectrum of the lightest scalars of the model. We show that Higgs mass of 125 GeV requires substantial radiative corrections. To do this, stops do not need develop a large mixing and must have mass around TeV. Moreover, some soft SUSY breaking terms may lie at the electroweak scale, which alleviates some tension concerning fine tuning of the related parameters. The lightest doubly charged scalar may have mass around few hundreds of GeV, which can be probed at the LHC, while the remaining scalars of the model have masses at TeV scale.